RATIONALIZATION OF THE NUSANTARA TAFSIR AND THE MIDDLE EAST: A COMPARATIVE STUDY OF THE INTERPRETATION OF AL-FĀTIHAH BY KH. ZAINI MUN’IM AND AHMAD MUSTAFĀ AL-MARĀGHĪ - Ubaidillah, Mohammad Mas’ud (Universitas Nurul Jadid, 2023)
The interpretation of the Qur’an continues to develop following the social, cultural, and geographical context—the interpretations of KH. Zaini Mun’im and Al-Marāghī have different characteristics and methods for understanding QS. Al-Fātihah. KH. Zaini Mun’im combines the bi al-ra’yi and Sufi approaches, while Al-Marāghī is known for his systematic and rational adabī ijtimā’ī style. Debates have arisen regarding the extent to which the rationality of the interpretations of Nusantara scholars can be compared with Middle Eastern scholars. This study analyzes the rationalization of KH Zaini Mun’im’s interpretation of Surah Al-Fātihah in Tafsīr Bi al-Imlā’ and Ahmad Musthafa Al-Marāghī in Tafsir Al-Marāghī. Another objective is to identify the uniqueness and characteristics of both interpretations and their relevance to the context of Nusantara society. This study uses a qualitative method with a library research approach. Data were obtained from primary sources in the form of Tafsīr Bi al-Imlā’ by KH. Zaini Mun’im and Tafsir Al-Marāghī by Ahmad Musthafa Al-Marāghī, as well as secondary sources in the form of books, journals, articles, and previous research. The analysis technique used is the comparative descriptive-analytical method. The results of the study indicate that both interpretations have similarities in the use of the tahlīlī method, but differ in approach. Tafsir Al-Marāghī uses the adabī ijtimā’ī style with simple and easy-to-understand language, while KH. Zaini Mun’im emphasizes the Sufi and contextual approach with a communicative language style—the interpretation of KH. Zaini Mun’im has a stronger relevance to the reality of Nusantara society. Finally, this study confirms the interpretation of Nusantara scholars, such as KH. Zaini Mun’im has rationality and contributions that are equal to the interpretation of Middle Eastern scholars. This can reduce the stigma of inferiority of Nusantara interpretation and add to the treasury of knowledge in the study of the Qur’an interpretation.